STUDY OF MICELLIZATION AND MICROEMULSION FORMATIONFOR SURFACE ACTIV AGENT IN OCTANOL AND WATERMIXTURE - Hassan, Sabeeh; Ahmad, Abdul Jalil (Iraqi Journal of Science, 2024)
A mixture of three components having different physical and chemical propertiesis represented by equilateral triangular diagram. Such a mixture produces variousregions on the interior of the triangular diagram. A system in each apex of thetriangle consists of two components.In this work, the effect of surface active agent on the micelle and microemulsionformation in a mixture, of octylphenyloxy-ethylene, octanol and water were studiedat 25°C.This mixture exhibits three regions. The appearance of these regions well fit withapproach that surface active agent can take several forms depending on theirconcentration in any mixture (22). The possible forms are monomer hexagonallyordered molecules or gonfeled micelles.